Charting a new course: ungraying the fleet and comprehensively supporting fishing livelihoods and communities - Ringer, Danielle; Donkersloot, Rachel; Carothers, Courtney (Frontiers in Sustainability, 2024)
This article provides perspectives on the graying of the fleet and research efforts to understand it in Alaska fisheries, discusses recent abrupt multifaceted challenges faced by Alaskan fishermen, and compares divergent public perceptions and support programs for farmers and fishermen in the United States. Equity concerns have seen a resurgence in academic and policy realms and the graying of the fleet is now a common example of distributional inequity, yet despite in-depth research attention on the issue, few substantive programmatic modifications have been made to address it in Alaska. Aging trends in United States fisheries have typically been framed as one of changing aspirational preferences. Research suggests coastal youth do desire and highly value fishing careers, but structural and financial barriers limit opportunities for new generations. The precarity of the fishing industry was highlighted in 2023 with sudden global seafood market instability, rising interest rates and operating costs, destabilized geopolitical tensions, and hastening climate change impacts. This recent industry turmoil disproportionately impacts those on the margins and adds an additional layer of complexity to addressing graying of the fleet trends. Unlike in fisheries, there are numerous federal programs to support young farmers and the agricultural industry. This paper calls for proactive and comprehensive measures to stabilize and support fishing communities and the viability of next generation pathways amidst recent fishing industry market turmoil and longer term inequities in fishery governance.